2007
DOI: 10.1302/0301-620x.89b6.18805
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term results of the Bernese periacetabular osteotomy in the treatment of symptomatic developmental dysplasia of the hip

Abstract: We studied the medium-term outcome of the Bernese periacetabular osteotomy in 52 patients (58 hips) with symptomatic developmental dysplasia of the hip and a mean age of 37.6 years (13 to 48). The operations were performed between 1993 and 2005 by the senior author with a mean follow-up of 66.7 months (13 to 153). There were 42 women (47 hips) and ten men (11 hips). Of these patients, 24 (30 hips) had an osteotomy on the right side and 22 (28 hips) on the left. Six patients had bilateral operations. The clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 31 publications
5
64
1
Order By: Relevance
“…Few long-term outcomes after PAO have been reported and to our knowledge ours is among the largest; in it, we aimed to define and analyze factors associated with longterm failure [2,7,17,21,28,31,33,40,43]. Our data suggest that the ideal candidate is younger than 25 years of age with adequate joint space width and good hip congruency.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Few long-term outcomes after PAO have been reported and to our knowledge ours is among the largest; in it, we aimed to define and analyze factors associated with longterm failure [2,7,17,21,28,31,33,40,43]. Our data suggest that the ideal candidate is younger than 25 years of age with adequate joint space width and good hip congruency.…”
Section: Discussionmentioning
confidence: 88%
“…DDH is a known cause of pain and is a substantial cause of morbidity in the young adult population [2,5,17]. Few studies have reported on activity-related and quality-of-life outcomes after PAO.…”
Section: Discussionmentioning
confidence: 99%
“…This reorientation medializes the joint center and reduces superolateral inclination, thus improving femoral head coverage [7,14]. Although recent studies have focused on assessing the medium-and longterm outcomes of PAO [10,11,15,24,27], neither the level of patient function nor the factors that influence clinical and functional outcome are well described [10,11,15,24,27] for an invasive procedure with a risk of major complications ranging from 6% to 37% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies report on the functional outcomes, predictors of outcomes, and survival rates for PAO and other acetabular reorientation osteotomies performed for symptomatic acetabular dysplasia [2,5,10,13,16,19,22,23]. The Bernese periacetabular osteotomy has reportedly led to good to excellent results for approximately 75% to 93% of patients [15,16,19,23].…”
Section: Introductionmentioning
confidence: 99%